2017
DOI: 10.1073/pnas.1712961114
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of heterochromatin inheritance by Dpb3–Dpb4 complex

Abstract: During DNA replication, chromatin is disrupted ahead of the replication fork, and epigenetic information must be restored behind the fork. How epigenetic marks are inherited through DNA replication remains poorly understood. Histone H3 lysine 9 (H3K9) methylation and histone hypoacetylation are conserved hallmarks of heterochromatin. We previously showed that the inheritance of H3K9 methylation during DNA replication depends on the catalytic subunit of DNA polymerase epsilon, Cdc20. Here we show that the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…Pol α was also important for heterochromatin silencing maintenance in fission yeast and the restoration of repressive histone marks in plants [159,160]. Similarly, it has been shown that both the Pol ε catalytic subunit Pol2 and the regulatory subunits Dpb3-Dpb4 are important for the maintenance of epigenetic states in subtelomeric regions and heterochromatin boundary specificity in budding yeast [161,162]. dpb3Δ and dpb4Δ cells also showed silencing loss at mating-type loci [158].…”
Section: Dna Polymerases: Key Players In Histone Segregation On Daughmentioning
confidence: 99%
“…Pol α was also important for heterochromatin silencing maintenance in fission yeast and the restoration of repressive histone marks in plants [159,160]. Similarly, it has been shown that both the Pol ε catalytic subunit Pol2 and the regulatory subunits Dpb3-Dpb4 are important for the maintenance of epigenetic states in subtelomeric regions and heterochromatin boundary specificity in budding yeast [161,162]. dpb3Δ and dpb4Δ cells also showed silencing loss at mating-type loci [158].…”
Section: Dna Polymerases: Key Players In Histone Segregation On Daughmentioning
confidence: 99%
“…Pol ε plays crucial roles in chromosome replication, cell cycling, and the repair of damaged DNA 17 . Both Dpb3 and Dpb4 are non-essential proteins that form a heterodimeric complex and bind to double-stranded DNA [18][19][20] . The Dpb3-Dpb4 complex physically associates with the Pol ε catalytic subunit, Cdc20, and also interacts with proteins that are important for heterochromatin assembly.…”
mentioning
confidence: 99%
“…Recent studies uncovered strand-specific pathways of parental histone recycling in nascent chromatin (He et al, 2017;Gan et al, 2018;Petryk et al, 2018;Yu et al, 2018). The transfer of parental histones H3-H4 to the lagging strand relies on the synergistic action of the histone chaperone Mini-Chromosome Maintenance Protein 2 (MCM2), a subunit of the MCM helicase, chromosome transmission fidelity 4 (CTF4), and the lagging strand-specific primase DNA polymerase α (Pol-α) (Huang et al, 2015;Gan et al, 2018;Petryk et al, 2018; Figure 1B).…”
Section: Recycling Of H3k27me3-marked Nucleosomes and Incorporation Omentioning
confidence: 99%
“…CTF4 anchors Pol-α in the vicinity of the MCM helicase, thus enabling the transfer of parental histones H3-H4 from MCM2 to the lagging stand via Pol-α. The transfer of parental histones H3-H4 to the leading strand depends on Dpb3-4, a heterodimer associated with the leading strand-specific DNA polymerase (Pol-) (He et al, 2017;Yu et al, 2018; Figure 1B ). Interestingly, asymmetric inheritance of parental histones H3-H4 in fission yeast lacking either Dpb3 or Dpb4 results in loss of heterochromatin integrity and transcriptional activation, which emphasizes the functional role of epigenetic inheritance in the maintenance of genome stability and transcriptional programs (He et al, 2017;Yu et al, 2018).…”
Section: Recycling Of H3k27me3-marked Nucleosomes and Incorporation Omentioning
confidence: 99%